Design of a porous biodegradable internal fixation for the treatment of pauwels type III femoral neck fractures - Liu, Chunsheng; Wang, Songyuan; Zhao, Yinuo; Shen, Ying; Zhang, Meng; Li, Haoqian; Wang, Yanqin; Xue, Yanru; Wu, Xiaogang; Chen, Weiyi; He, Liming (Frontiers in Bioengineering and Biotechnology, 2025)
Prolonged internal fixation in the femur can cause issues like osteosclerosis and stress masking, which hinder fracture recovery. AZ31b magnesium alloy has already been widely investigated and shown to be biocompatible and biodegradable. This study used finite element analysis to investigate stress changes during healing, aiming to find the best time for removing internal fixation and focuses on optimizing the structural design of internal fixation, using AZ31b magnesium alloy, to address issues like osteosclerosis and stress shielding in femoral neck fracture healing. This study focuses on optimizing structural design for the treatment of Pauwels III femoral neck fractures using cannulated screws. Pauwels III fractures are characterized by high shear stress and unstable fracture angles, making them prone to fixation failure. By optimizing the fixation method, the risk of complications such as osteosclerosis and stress shielding can be mitigated, ultimately improving clinical outcomes. The findings show that when cancellous bone heals but cortical bone does not, stress on the fracture surface decreases. Early removal of titanium internal fixation, followed by biodegradable porous internal fixation, allows for natural degradation during healing. We simulated stress evolution across healing stages via finite element modeling to determine optimal fixation replacement timing. Four AZ31b magnesium alloy porous structures (cubic, honeycomb, diagonally orientated, modified truncated pyramid) were designed; their equivalent elastic modulus and strength were evaluated through simulated compression tests, while permeability was analyzed using computational fluid dynamics (CFD). We found that the cubic and honeycomb structures were found to have higher permeability (6.23 × 10-7 m2, 1.636 × 10-7 m2) and have high elastic modulus (8.422Gpa, 14.694Gpa) which can match the elastic modulus of human bone. Optimal structures were then applied to an inverted triangular screw group model for biomechanical validation post-femoral neck fracture fixation. Finite element analysis of a Pauwels III femoral neck fracture model indicated that the honeycomb porous internal fixation had superior mechanical properties. In conclusion, this study proposed a solution to osteosclerosis and stress masking after femoral neck fracture surgery.